Description of Consumption Patern and Work Fatigue of Online Motorcyle Taxi Riders During The Covid-19 Pandemic in Kupang City - Sagi, Elviani Stevani; Nur, Marselinus Laga; Boeky, Daniela L. A (Timorese Journal of Public Health, 2022)
Eating behavior is a person's response to food as a vital need for life, including knowledge, attitudes, and practices towards food and the elements contained therein. The job of being an online motorcycle taxi driver has its own challenges. Uncertain income and time to get passengers are one of the factors that most drivers have irregular eating patterns and do not consume nutritious foods. This can cause fatigue and will decrease work productivity. During the Covid-19 Pandemic in Kupang City, this study was done to learn more about the eating habits and level of job tiredness of online motorcycle taxi drivers. This kind of research uses quantitative analysis to study descriptive data. A sample of 96 people and all online motorcycle taxi drivers (Grabbike) in Kupang City made up the study's population. A food frequency questionnaire and the IFRC scale were used in the data collection process during interviews. The findings revealed that 62.5 percent of attitudes toward food intake and 86.5 percent of knowledge of healthy food were in the good categories, respectively, for online motorcycle taxi drivers. Rice as a main cuisine, eggs, tempeh, kale, bananas, and coffee are the foods that online motorbike taxi drivers consume the most frequently. Food frequency falls into the less frequent category at 72.9 percent, and work tiredness falls into the medium category at 89.6 percent. Online motorcycle taxi drivers need to eat a balanced diet of healthy foods, drink more variety, and get enough sleep in order to put their knowledge to use